The green tailgate: alternative approach to stormwater management at sports venues - Graber, Jay (Kansas State University, 2010)
Sports venues require large amounts of parking to facilitate the number of spectators attending an event. The parking, mostly surface, is underutilized when compared to traditional parking lots accommodating daily use. Large parking surfaces alter the natural hydrological cycle by generating large volumes of runoff. Over time, pollutants build up on a parking surface and are discharged into a stormwater drainage system during a rain event. The intent of the research is to investigate the use of Best Management Practices that ultimately reduce the pollutant loads created by stormwater runoff while creating amenities for spectators that could potentially generate revenue. The focus of the study will be on a 400 acre sports venue in Kansas City, Missouri, the Truman Sports Complex. To understand retrofitting stormwater management practices, one must understand how large parking lots are constructed and understand successful examples. Through the use of archival research, interviews and analysis of two parking lot case studies, Northgate Mall in Seattle, Washington and US Cellular Field in Chicago, Illinois, the research analyzed how retrofitting design solutions are utilized to reduce stormwater pollutant loads. Each case study documents a distinct type of retrofitting strategy; bioswales at Northgate Mall and permeable concrete pavers at US Cellular Field. Using the Design Point Method developed by the Center for Watershed Protection, the research analyzes each case study retrofit design solution - conceptually and post construction. The Design Point Method allowed the research to measure the success of retrofitting strategies and informed the research to as to how the strategies could be implemented at the Truman Sports Complex. The conclusion of the project is a retrofit design solution of a surface parking lot at the Truman Sports Complex. Using the Design Point Method as an analysis tool, the final study provides compelling evidence that retrofitting existing surface parking lots at sports venues using Best Management Practices provides a sustainable solution to reducing pollutant loads while creating the potential for enhancing the tailgate experience for the sports fan.
Keywords: Stormwater Management; Landscape Architecture (0390)